Silahlara veda - Hemingway, Ernest Miller, 1899-1961. (Istanbul : Oda, 1995)
An American ambulance officer serving on the Austro_Italian front deserts to join an English nurse after the retreat of Caporetto.
This book is in Turkish.
Keywords: World War I -- 1914-1918 -- Fiction